Mindfulness untuk Menurunkan Stres pada Ibu Rumah Tangga di Desa Ledug - Sumarni, Tri; Andini, Amelia; Septiani, Febi (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
Stay-at-home moms often face unique stressors and challenges in their daily lives, which can impact their well-being and sleep quality. Stress as a source of physical and mental health disorders in housewives. There is evidence in the literature that stress can reduce the effectiveness of the human immune system and increase the risk of infection. One effective intervention to improve the health and happiness of housewives is mindfulness techniques. The aims of this activity are (1) increasing knowledge about stress and its impact on health (2) increasing skills in mindfulness techniques to reduce stress (3) reducing degenerative diseases such as hypertension and diabetes mellitus which are caused by stress. The method for implementing this activity is giving a pre-test, post-test about stress before and after education, providing training on mindfulness techniques which begins with giving a questionnaire about mindfulness. This activity was attended by 17 PKK mothers in Ledug Village. Most service participants are early adults (32-45 years) (64.7%), have higher education (50%) and most do not work (71%). Regarding stress levels, before training stress levels were mostly in the moderate stress category (74%) and after training stress levels were in the mild stress category (82%). Meanwhile, for the level of mindfulness, before counseling most were in the moderate mindfulness category (70.5%) and after counseling most were in the high mindfulness category (88.2%).